(3QSGdI eNJUQI aj Yde GdHOjYs ((3bQjI GdSdGeI (B_ (3GdWGFa s)
(3ChdgG (B:s
(3Yhfc Gddge ef UfYI GdTYQ ddYScQi ETJbGb GdHOjY EfeG CQGO GdeMOKhf Hbhdge GdHOjY EfeG GQGO GdeMOKhf Hbhdge GdHOjY s
(3BNQgG (B:s
(3abGd di NeShf UOjbkG Hjf bGVi hTQja Ph RjQ hGjQ habjg hXQja hdh EMJLJ Edjge eG hahG di HQZja Je GdcJGH HYhf Gddg Gdedc GdhgGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdeLGejYs